Effect of pemetrexed on brain metastases from nonsmall cell lung cancer with wild-type and unknown EGFR status. Issue 3 (January 2019) - Yu, Xiaoqing; Fan, Yun
Abstract : Abstract: We aimed to evaluate the effectiveness of pemetrexed-based chemotherapy in wild-type nonsmall-cell lung cancer (NSCLC) patients with brain metastases (BM). Brain metastases are a common cause of mortality in NSCLC patients. For epidermal growth factor receptor (EGFR) wild-type patients, therapeutic options for BM are even limited. Pemetrexed-based therapy is a standard care for patients with EGFR-negative, nonsquamous NSCLC. Besides local therapy, pemetrexed is the preferred chemotherapy for wild-type BM patients, but the efficacy is uncertain. We retrospectively studied 138 NSCLC patients with BM whose EGFR status were unknown or wild-type. All patients received first-line pemetrexed-based chemotherapy from 2010 to 2015. Forty-six of 89 patients with unknown EGFR status were treated with EGFR TKIs after progression. Among the 138 patients, 49 (35.5%) were EGFR wild-type and 89 (64.5%) were unknown EGFR status. The median overall survival (OS), and the median intracranial progression-free survival (iPFS) was 21.0 months, 9.5 months, respectively. Patients who received more than 4 cycles of chemotherapy had significantly longer OS than those who received 3 to 4 cycles (Mantel-Byar X-squared = 6.65, P = .001). In the EGFR wild-type group, the median OS, and the median iPFS was 17.7 months, 7.6 months, respectively. And patients treated with pemetrexed plus platinum tended to have a longer OS than those who were treated with pemetrexed alone ( P = .078). In the subgroup with unknown EGFR status, we noted a statistically significant improvement in OS for the patients who received EGFR tyrosine kinase inhibitors (TKIs) after progression of 29 months compared to 20.3 months of the EGFR TKIs naïve arm ( P = .027). Pemetrexed shows an ideal effectiveness in EGFR wild-type and unknown status NSCLC patients with BM, and has a favorable control on brain localizations. EGFR wild-type patients can significantly benefit from pemetrexed continuation maintenance.